Introduction of self-control of enterprise information system through accounting documentation process of - K.О. Volskа (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The research is devoted to determining the possibility of implementing self-control of an enterprise information system, describing the criteria for building an information system in an enterprise that will be self-organized and capable of self-analysis. The article considers the concept of self-control, its main criteria as well as the possibility of implementing the self-control in the information system of the enterprise. The current study provides the definition of intelligent information systems and how to use expert knowledge in them. The article presents the place of the self-control (in terms of its organization at the enterprise) in the economic activity of the enterprise and its correlation with internal control; as a result, it is suggested to consider the self-control of the information system as the unit included in the methods of internal control. The paper carries out the comparison of the response to the error in the information system under the usual control (from the subject of the control to the person) and the self-control, that made it possible to determine the latter as the method of preventing errors, that is, real-time control during the data entry in the information system of the enterprise. It is proposed to divide the control mechanisms in the information system into informational (protection of the information system from a technical point of view) and special (accounting, legal, technological, etc.). The special control mechanisms of the information system should initially be formed by the experts of the relevant profile and who should present them in the form of algorithms for preventing any possible errors that will allow IT-professionals to describe them at the software level and implement one of the criteria for self-control of the information system, namely, a self-examination. The article proposes to implement the self-control at the input of the information system, when entering the data of the primary documents into the database, as there is a high probability of occurrence of errors right here.